Relevance of chronic hepatitis E in liver transplant recipients: a real‐life setting. Issue 4 (14th July 2015) - Galante, A.; Pischke, S.; Polywka, S.; Luetgehethmann, M.; Suneetha, P.V.; Gisa, A.; Hiller, J.; Dienes, H.P.; Nashan, B.; Lohse, A.W.; Sterneck, M.
Abstract The chronic course of hepatitis E virus (HEV) infections in orthotopic liver transplant (OLT) recipients has been described previously, but prospectively collected data are rare. We aimed to study the role of chronic hepatitis E in OLT in a real‐life setting. Therefore, 287 adult OLT recipients (169 male [59%], median age 56 years) were prospectively tested by HEV polymerase chain reaction assay (lower level of detection = 10 IU/mL), irrespective of their level of liver enzymes. In 4 patients (1.4%), chronic HEV infection was diagnosed. All 4 patients were male, and their age (median 48.5 years), the time since transplantation (median 45.5 months), and bilirubin level (median 0.6 mg/dL) did not differ significantly from the total cohort. However, alanine transaminase and aspartame transaminase levels were significantly higher in HEV‐infected patients (75–646 U/L, median 216 U/L and 68–317 U/L, median 108 U/L) than in non‐infected patients (6–617 U/L, median 41 and 6–355 U/L, median 36; P = 0.004 and 0.040, Mann–Whitney test). In 3 patients, liver biopsy was performed and revealed signs of inflammation and chronic liver disease, as enlarged densely infiltrated portal tracts with mild‐to‐moderate interface hepatitis. All infected patients were treated with ribavirin with the starting dose adjusted to renal function (400–800 mg/day). In 2 patients, dose reduction was necessary. Transaminases normalized in all 4 patients, and all patients cleared their infection within 3 months of ribavirin treatment. However, 1 patient experienced viral relapse 12 weeks after discontinuation. Ribavirin medication was re‐started and viral clearance occurred within 8 weeks and persisted. Sequence analysis of the HEV genome of this patient revealed that he was infected with an HEV variant, which recently has been shown to have a reduced response to ribavirin in cell culture. The risk of chronic HEV infections in OLT recipients in low‐endemic countries should not be overestimated. No case of chronic hepatitis E was observed in patients with normal liver enzymes, indicating that general screening of all OLT recipients is not necessary. However, if chronic hepatitis E develops, it can be treated efficiently with ribavirin.